'Slashing the Teddy Bear's Tummy with a Carving Knife': The Infanticidal Roots of Schizophrenia. (25th July 2019) - Kahr, Brett
Abstract : In this article, the author explores the complex controversies surrounding the aetiology of the schizophrenic psychoses. After reviewing the historical literature, the author discusses the ongoing debate between the opposing biopathological and psychoanalytical models of causation. In particular, he examines the considerable, but often neglected, body of evidence in support of a theory of the traumatogenic origin of the severe psychoses, including not only clinical but also empirical psychopathological research, especially findings from Holocaust studies. Drawing upon his own psychoanalytical work with psychotic patients over many decades, the author proposes a theory of aetiology based on the widespread occurrence of conscious and unconscious parental death wishes in the early histories of individuals who later became diagnosed as schizophrenic. He traces the development of his concepts of 'psychological infanticide' and the 'infanticidal introject', providing clinical illustrations of the ways in which early death wishes towards babies and children impact upon the subsequent onset of psychopathology.